Synthesis and electrochemical characterization of Si/TiO2/Au composite anode: Efficient oxygen evolution and hydroxyl radicals generation - Bessegato, G. G. [UNESP]; Cooke, M. D.; Christensen, P. A.; Wood, D.; Zanoni, M. V.B. [UNESP] (Elsevier, 2021)
This paper describes the photoelectrochemical properties of a novel composite anode composed of a 200 nm Au-Sb ohmic contact/300 μm n-Si wafer/20 nm TiO2 /120 nm Au grid. By connecting the Au ohmic contact to the gold grid via a power supply, holes thermally or photochemically generated in the Si are launched to the TiO2 surface where they are converted to •OH radicals. We show that the Si/TiO2/Au composite anode can be efficiently employed in the oxygen evolution reaction and prove that the anode generates hydroxyl radicals (using p-nitrosodimethylaniline as a probe). Potential applications include the photoelectrocatalytic oxidation of organic contaminants, water splitting, and organic electro-synthesis.
Keywords: Dye degradation; Oxygen generation; Photoelectrochemistry; Titanium dioxide